Diagnostic evaluation of a deep learning model for optical diagnosis of colorectal cancer - Dejun Zhou (Nature Portfolio, 2020)
Colonoscopy is the most commonly used tool to screen for colorectal cancer (CRC). Here, the authors develop a deep learning model to perform optical diagnosis of CRC by training on a large data set of white-light colonoscopy images and achieve endoscopist-level performance on three independent datasets.